2021
DOI: 10.1002/ajh.26365
|View full text |Cite
|
Sign up to set email alerts
|

Fecal microbiota transplantation with ruxolitinib as a treatment modality for steroid‐refractory/dependent acute, gastrointestinal graft‐versus‐host disease: A case series

Abstract: Acute graft-versus-host disease (aGvHD), together with infections, constitute the two main early complications of allogeneic hematopoietic cell transplantation (alloHCT). 1 The mainstay of first-line therapy in aGvHD is systemic administration of high-dose glucocorticoids, but only 40%-60% of patients respond to this treatment depending on the grade of severity of the disease. 1 At present, there is no established standard-of-care second-line therapy. The high mortality rate of steroid-refractory/dependent (sr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 5 publications
(9 reference statements)
0
9
0
Order By: Relevance
“…Further studies confirmed these findings [ 193 , 197 , 199 , 206 , 207 ]. Also, Bilinski’s team have shown the promising results of FMT as an immunomodulatory agent in the treatment of acute gastrointestinal graft-versus-host disease [ 208 , 209 ] what was confirmed in other groups [ 210 ].…”
Section: Therapeutic Strategies In the Gut Microbiota Manipulationmentioning
confidence: 80%
“…Further studies confirmed these findings [ 193 , 197 , 199 , 206 , 207 ]. Also, Bilinski’s team have shown the promising results of FMT as an immunomodulatory agent in the treatment of acute gastrointestinal graft-versus-host disease [ 208 , 209 ] what was confirmed in other groups [ 210 ].…”
Section: Therapeutic Strategies In the Gut Microbiota Manipulationmentioning
confidence: 80%
“…Our previous work shows the remarkable efficacy of FMT in preventing colonization of a single, in that case, antibiotic-resistant bacteria ( 118 ). Also, in the model of graft-versus-host disease, we have shown that it is possible to stop the inflammatory process in the gut by FMT, shedding new light on the immunomodulatory effect of the gut microbiota ( 119 , 120 ). Given that single species of bacteria, Klebsiella and Streptococcus were shown to play a role in the progression of MM, it seems that further studies on gut microbiota in the treatment of MM are warranted.…”
Section: Discussionmentioning
confidence: 95%
“…As the patients with gut GvHD are often colonized with antibiotic-resistant bacteria (ARB), there are pioneer studies of experience performing FMT in patients with acute or chronic GvHD, co-colonized with ARB. These studies have shown a good efficacy of FMT in the treatment of GvHD and decolonization of the GI tract from ARB [160,161].…”
Section: Graft-versus-host Diseasementioning
confidence: 93%
“…Complications from the procedure comprise most of all infections and GvHD, which are the major causes of morbidity and mortality (45% of attributable deaths) apart from relapse [160]. The first-line therapy in acute GvHD is systemic administration of high-dose glucocorticoids, but only 40-60% of patients respond to this treatment depending on the grade of severity of the disease [161]. At present, there is no established standard-of-care second-line therapy.…”
Section: Graft-versus-host Diseasementioning
confidence: 99%
See 1 more Smart Citation